2021
DOI: 10.1002/jbm.b.34802
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatiblemagnesium‐dopedbiphasic calcium phosphate for bone regeneration

Abstract: Autologous bone grafting remains the gold standard for almost all bone void‐filling orthopedic surgery. However, autologous bone grafting has several limitations, thus scientists are trying to identify an ideal synthetic material as an alternative bone graft substitute. Magnesium‐doped biphasic calcium phosphate (Mg‐BCP) has recently been in the spotlight and is considered to be a potential bone substitute. The Mg‐BCP is a mixture of two bioceramics, that is, hydroxyapatite (HA) and β‐tricalcium phosphate (β‐T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Previous studies have shown the application of calcium phosphate materials in many fields, especially in bone grafts (Ballouze et al, 2021;Dejob et al, 2021;Lodoso-Torrecilla et al, 2021). In an experiment conducted earlier, we considered extracting calcium phosphate materials from fishery waste.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the application of calcium phosphate materials in many fields, especially in bone grafts (Ballouze et al, 2021;Dejob et al, 2021;Lodoso-Torrecilla et al, 2021). In an experiment conducted earlier, we considered extracting calcium phosphate materials from fishery waste.…”
Section: Discussionmentioning
confidence: 99%
“…These factors lead to improved cell adhesion, proliferation, and metabolic activity [ 43 ]. A mixture of HA and β-TCP doped with Mg (magnesium-doped biphasic calcium phosphate) mimics the natural inorganic bone matrix with excellent physicochemical properties [ 44 ]. Furthermore, the presence of Mg ions during synthesis also improves the thermal stability of HA and produces a more stable phase composition after heat treatment, which enables the production of porous or granulated scaffolds for biomedical applications, including oral and maxillofacial surgery and orthopedics [ 44 , 45 ].…”
Section: Bioresorbable Mg-based Materials For Guided Bone Regeneratio...mentioning
confidence: 99%
“…that make it suitable for use in various applications (implantology, dentistry, etc.) in the medical field [ 8 , 9 , 10 ]. To improve the properties of hydroxyapatite and provide it with antimicrobial activity, we chose to dope HAp with magnesium (Mg 2+ ).…”
Section: Introductionmentioning
confidence: 99%